2004
DOI: 10.1096/fj.03-0573fje
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of endothelial cells triggers a caspase‐dependent anti‐apoptotic paracrine loop active on vascular smooth muscle cells

Abstract: Increased endothelial apoptosis and decreased apoptosis of vascular smooth muscle cells (VSMC) are central to initiation of myo-intimal thickening. We hypothesized that apoptosis of endothelial cells (EC) induces the release of anti-apoptotic mediator(s) active on VSMC. We found that serum-free medium conditioned by apoptotic EC decreases apoptosis of VSMC compared with fresh serum-free medium. Inhibition of endothelial apoptosis during conditioning with a pan-caspase inhibitor ZVAD-FMK blocked the release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 39 publications
8
119
1
Order By: Relevance
“…To study the secretome of apoptotic EC, human umbilical vein endothelial cells (HUVEC) were rendered apoptotic in vitro by serum starvation (SS) for 4 h, as reported previously. [3][4][5][6][7][8] In serum-starved EC, the percentage of cells with chromatin condensation in absence of cell membrane permeabilization increased over time, suggesting increased apoptosis ( Figure 1a). The absence of lactate dehydrogenase (LDH) release in serum-starved EC was also consistent with absence of cell membrane permeabilization ( Figure 1b Characterization of the secretome of apoptotic EC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the secretome of apoptotic EC, human umbilical vein endothelial cells (HUVEC) were rendered apoptotic in vitro by serum starvation (SS) for 4 h, as reported previously. [3][4][5][6][7][8] In serum-starved EC, the percentage of cells with chromatin condensation in absence of cell membrane permeabilization increased over time, suggesting increased apoptosis ( Figure 1a). The absence of lactate dehydrogenase (LDH) release in serum-starved EC was also consistent with absence of cell membrane permeabilization ( Figure 1b Characterization of the secretome of apoptotic EC.…”
Section: Resultsmentioning
confidence: 99%
“…6 Concomitantly, SSC-Apo was fractionated by fast protein liquid chromatography (FPLC), and the antiapoptotic activity of each fraction was evaluated on VSMC. 3 The protein mediators present in fractions with significant antiapoptotic activity were further characterized by SDS-PAGE LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two different bioactive molecules were selected to create a bioactive coating: (i) chondroitin sulfate (CS), a glycosaminoglycan of the extracellular matrix that participates in the integrity of the arterial wall in normal aortas [9] and exhibits anti-apoptotic properties [10]; and (ii) epidermal growth factor (EGF), a major actor of wound-healing [11] presenting both anti-apoptotic and pro-proliferative properties [12,13]. This choice is based on previous studies that have shown the superiority of the combination of CS and EGF [14].…”
Section: Methodsmentioning
confidence: 99%